Harnessing biological synthesis: Zinc oxide nanoparticles for plant biotic stress management - Verma, Naveen; Kaushal, Priya; Sidhu, Amanpreet K. (Frontiers in Chemistry, 2024)
Crop growth and yield are negatively impacted by increased biotic stress in the agricultural sector due to increasing global warming and changing climatic patterns. The host plant’s machinery is exploited by biotic stress, which is caused by organisms like bacteria, fungi, viruses, insects, nematodes, and mites. This results in nutrient deprivation, increased reactive oxygen species and disturbances in physiological, morphological, and molecular processes. Although used widely, conventional disease management strategies like breeding, intercropping, and chemical fertilizers have drawbacks in terms of time commitment and environmental impact. An environmentally beneficial substitute is offered by the developing field of nanotechnology, where nanoparticles such as zinc oxide are gaining popularity due to their potential applications as antimicrobials and nano-fertilizers. This review delves into the biological synthesis of ZnO nanoparticles employing plants and microbes, function of ZnO nanoparticles in biotic stress mitigation, elucidating their effectiveness and toxicological implications in agricultural. This study supports a cautious approach, stressing the prudent application of ZnO nanoparticles to avoid possible toxicity, in line with the larger global agenda to end hunger, guarantee food security, and advance sustainable agriculture.